Short Communication: A report on ranging behavior of Malayan flying lemurs, Galeopterus variegatus, in West Indonesia: Relationships with habitat characteristics - YAMATO TSUJI; BAMBANG PRAYITNO; TAKAFUMI TATEWAKI; KANTHI ARUM WIDAYATI (Biodiversitas Journal of Biological Diversity, 2019)
Tsuji Y, Prayitno B, Tatewaki T, Widayati KA, Suryobroto B. 2019. Short Communication: A report on ranging behavior of Malayan flying lemurs, Galeopterus variegatus, in West Indonesia: Relationships with habitat characteristics. Biodiversitas 20: 430-435. We attached GPS telemeters to wild Malayan flying lemurs, or colugos (Galeopterus variegatus) (n = 3, one adult male, one adult female, one juvenile male) in Pangandaran Nature Reserve, West Java, Indonesia in August 2018, to preliminary evaluate their home range size and characteristics, paying special attention to relationships with forest structure. Home range sizes, generated from location points collected from 4 to 11 days, ranging from 1.2 to 5.4 ha (based on minimum convex polygon method) or from 1.3 to 4.2 ha (95% Kernel), which is much larger than home ranges of colugos inhabiting palm plantations. The home range sizes of adult colugos were larger than that of juvenile. The home ranges of an adult female and a juvenile overlapped. The generalized linear model demonstrated that the locations where the colugos stayed frequently possessed a small number of trees and/or had a single taller tree, and these effects were stronger than other factors. The home range preferences of colugos seem to be related to gliding effectiveness and/or predator avoidance. The mean gliding distances were 33 m, but sometimes reached > 250 m, and there were no significant differences among animals. Night time gliding frequency showed no clear difference between time periods. We confirmed the effectiveness of GPS telemetry for tracking colugo movements.